Preterm children’s developmental coordination disorder, cognition and quality of life: a prospective cohort study - Paivi Rautava; Liisi Ripatti; Mari Koivisto; Leena Haataja; Liisa Lehtonen; Karoliina Uusitalo; Anna Nyman; Mira Huhtala; Riitta Parkkola; Katri Lahti; Sirkku Setänen (BMJ Paediatrics Open)
Objective To evaluate the rate of developmental coordination disorder (DCD) and its correlation to cognition and self-experienced health-related quality of life (HRQoL) in children born very preterm.Design Prospective follow-up study.Setting Regional population of children born very preterm in Turku University Hospital, Finland, in 2001–2006.Patients A total of 170 children born very preterm were followed up until 11 years of age.Main outcome measures Motor and cognitive outcomes were evaluated using the Movement Assessment Battery for Children - Second Edition (Movement ABC-2) and the Wechsler Intelligence Scale for Children - Fourth Edition, respectively, and HRQoL using the 17-Dimensional Illustrated Questionnaire (17D). The Touwen neurological examination was performed to exclude other neurological conditions affecting the motor outcome.Results Eighteen children born very preterm (17 boys) (11.3%) had DCD, defined as Movement ABC-2 total test score ≤5th percentile. A positive correlation between motor and cognitive outcome (r=0.22, p=0.006) was found. Children born very preterm with DCD had lower cognitive scores than those without DCD (Full-Scale IQ mean 76.8 vs 91.6, p=0.001). Moreover, children born very preterm with DCD reported lower HRQoL than children born very preterm without motor impairment (17D mean 0.93 vs 0.96, p=0.03). However, HRQoL was higher in this group of children born very preterm compared with population-based normative test results (p<0.001).Conclusions DCD was still common at 11 years of age in children born very preterm in 2000s. DCD associated with adverse cognitive development and lower self-experienced HRQoL. However, this group of children born very preterm reported better HRQoL in comparison with Finnish norms.